Evaluation of Local Scour along the Base of Longitudinal Training Walls (2023)
This study proposes a new empirical model for estimating local scour along the base of longitudinal training walls for granular riverbeds. The model’s performance was rigorously assessed through experiments conducted in an open-channel flume, encompassing variations in granulometric characteristics, slope, and flow rates. The investigation involved a comparative analysis of six commonly employed equations for scour estimation. The results consistently demonstrated a tendency of the selected equations to overestimate scour depth within the longitudinal structures. In contrast, the new proposed equation considers factors such as the well-graded granular bedding represented by the Coefficient of uniformity (Cu) and the embedment of the longitudinal wall. This allows for a more robust identification of the scour behavior of longitudinal walls. This research enhances our comprehension of local scour in riverbeds. It provides engineers and researchers with a valuable tool for more accurate predictions, thereby contributing to the improved design and maintenance of river environment structures.